Analysis of the influence of educational level on the nutritional status and lifestyle habits of the young Spanish population - Sandri, Elena; Pardo, Juan; Cantín Larumbe, Eva; Cerdá Olmedo, Germán; Falcó, Antonio (Frontiers in Public Health, 2024)
Aim This study aims to analyze some nutrition and health habits of young people and the impact of educational attainment on health. Methods An observational, descriptive, and cross-sectional study was carried out using surveys. Using non-probabilistic snowball sampling, a previously validated questionnaire was disseminated through networks, collecting a sample of 9,681 people between 18 and 30 years old. Comparative analyses between groups were obtained by clustering and the corresponding statistical tests. Results The results showed how young people with higher education generally have a lower BMI, a higher healthy nutrition index, less frequent consumption of sugary drinks, and less smoking than their peers with basic education. These healthier habits are reflected in the higher self-perceived health status of the higher-educated group. While for all the educational levels analyzed, the minutes of physical activity practice are above the 150 min recommended by the WHO. Conclusion Our findings suggest that young people’s education level is of fundamental importance for health, particularly for nutritional habits. In general, the lifestyle habits of the young Spanish population are healthy, but there is a need for improvement in those aspects related to nutrition and food.